Pyrazole‐promoted synthesis of pyrrolo[3,4‐c] quinoline-1,3‐diones in a novel diketene-based reaction - Rezvanian, Atieh; Esfandsar, Zahra (Frontiers in Chemistry, 2023)
We describe the first classic example of green synthesis of pyrrolo [3,4-c]quinolones scaffolds by catalyst-free unusual reaction of diketene, isatin, and primary amines in ethanol in the presence of pyrazole as a promoter for four hours. The whole structure of the new product was confirmed by Xray analysis. The overall transformation involves the cleavage and generation of multiple carbonnitrogen and carbon-carbon bonds. This report represents a simple and straightforward approach for the synthesis of pyrrolo [3,4-c]quinoline-1,3-diones, which has significant advantages like readily available precursors, non-use of toxic solvent, operational simplicity, mild conditions, good atom economy, and excellent yields; therefore it provides a green and sustainable strategy for access to a range of interesting N-containing heterocyclic compounds in medicinal and organic chemistry.